ANALISIS KEBERLANJUTAN PROGRAM DAERAH PERLINDUNGAN LAUT DENGAN PENDEKATAN ANALYTIC HIERARCHY PROCESS (AHP) DI KABUPATEN RAJA AMPAT - Hamid, Hamid (Bumi Lestari, 2012)
The aims of this research were (1) to assess the sustainability of the marine sanctuary program in the COREMAP site phase II Raja Ampat; and (2) to find out the parameters which affect the sustainability aspects marine sanctuary program in the COREMAP site phase II Raja Ampat. This research had been conducted in Raja Ampat-West Papua by using survey method and respondents determined by purposive sampling method. The collected data had been analyzed by Analytic Hierarchy Process, or AHP. The results indicated that (1) the sustainability of marine sanctuary program in the COREMAP site phase II Raja Ampat will go on, because the strong indications showed that the comprehensive sustainable value were 2,178 (high category), (2) from 22 evaluated villages, 15 villages (68,2%) have sustainability value by high category and 7 villages (31,8 %) have sustainability value by moderate category (i.e: Villages of Saonek, Yenbeser, Kurkapa, Bianci, Selpele, Yensawai, and Arefi).
Keywords: Sustainability; marine sanctuary; Analytic Hierarchy Process; Coremap II; Raja Ampat